PENGARUH TUMPANG SARI SAWI (Brassica juncea L.) DAN TOMAT (Solanum lycopersicum L.) TERHADAP POPULASI DAN TINGKAT SERANGAN ULAT TRITIP (Plutella xylostella L.) DI DESA KEBUN IX MUARO JAMBI - Yunita, Wilma; Saputri, Dewi; Asniwita, Asniwita (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2026)
Mustard greens (Brassica juncea ) is one of the horticultural commodities that is widely cultivated to meet community needs. The productivity of mustard greens in Jambi Province is relatively low compared to the potential yield of mustard greens. One of the causes of the low productivity of mustard greens in Jambi Province is the attack of Plutella xylostella pests on mustard plants, so it is necessary to control them. One control that can be carried out is technical culture, namely by implementing an intercropping pattern with repellent plants. One of the plants that can act as a repellent plant is the tomato plant. The aim of this research was to determine the effect of intercropping mustard greens and tomatoes on the population and intensity of P. xylostella attacks. This research was carried out by comparing two treatments, namely the monoculture planting pattern of mustard greens and the intercropping pattern of mustard greens with tomatoes. The results of the research showed that the population, intensity of P. xylostella attacks and production in the intercropping pattern of mustard greens with tomatoes were significantly higher compared to the mustard monoculture planting pattern. The tomato plants in this study have the potential to reduce the population and intensity of P. xylostella attacks on mustard greens.